Profil Resistensi Antibiotik pada Isolat Aeromonas hydrophila dari Sampel Klinis Ikan Nila dan Ikan Gurame - Rahmaniar, Reina Puspita; Widhowati, Dyah; Candra, Aditya Yoppy Ro (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to determine the antibiotic resistance profile of Aeromonas hydrophila isolated from clinical samples of Nile tilapia (Oreochromis niloticus) and gourami (Osphronemus goramy) showing disease symptoms. The research method involved sampling fish organs exhibiting anatomical pathological changes, followed by bacterial isolation using MacConkey Agar. Bacterial identification was conducted through Gram staining and biochemical tests, including TSIA, SIM, MR, VP, Simmons Citrate Agar, urease, and catalase tests. Isolates identified as A. hydrophila were subsequently tested for antibiotic susceptibility using the Kirby–Bauer disk diffusion method on Mueller Hinton Agar. Eight antibiotics were evaluated, namely ciprofloxacin, tetracycline, erythromycin, cefotaxime, ampicillin, gentamicin, streptomycin, and nalidixic acid. The results showed that four A. hydrophila isolates were obtained from a total of 20 fish samples examined. Antibiotic susceptibility testing revealed that two out of four isolates (50%) were resistant to ampicillin and one isolate (25%) was resistant to streptomycin, while all isolates remained sensitive to ciprofloxacin, tetracycline, erythromycin, cefotaxime, gentamicin, and nalidixic acid. In conclusion, the presence of antibiotic resistance in A. hydrophila, particularly to certain β-lactam and aminoglycoside antibiotics, indicates the need for continuous monitoring and prudent use of antibiotics in aquaculture practices to prevent the further development and spread of resistant pathogenic bacteria.